Magnetostratigraphy of ODP sites 114-701 and 114-702 - Bradford M Clement; Ernie A Hailwood (PANGAEA, 1991)
During Leg 114 of the Ocean Drilling Program 12 holes were drilled at seven sites in the subantarctic South Atlantic Ocean. A major objective of this cruise was to document the development of the deep-water passageway that formed as the Meteor and Islas Orcadas rises rifted and spread apart. We report here the results of a magnetostratigraphic study of the sediments recovered at Site 701, a deep-water site located within the gateway, and Site 702, a shallow-water site located near the crest of the Islas Orcadas Rise. The sequence of Pliocene-Pleistocene reversals observed at Site 701 is readily correlated with the Brunhes Chron through Chron C3A. Although correlation is more difficult in the older sections at Site 701 because of coring gaps and the lack of tight biostratigraphic control, it is possible to correlate the late Miocene sequence of reversals with Chrons C4A and C5. The polarity sequence observed in the very weakly magnetized middle to upper Eocene nannofossil chalks recovered from Hole 702B is correlated with Chrons C18 through C21. The correlation of the polarity sequences at these two sites provides a temporal framework for these sediments and makes it possible to calibrate southern high-latitude biostratigraphic datums to the geomagnetic polarity time scale.
Supplement to: Clement, BM; Hailwood, EA (1991): Magnetostratigraphy of sediments from sites 701 and 702. In: Ciesielski, PF; Kristoffersen, Y; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 114, 359-366, https://doi.org/10.2973/odp.proc.sr.114.156.1991